P5 Berbasis Ecoprint Untuk Pendidikan Karakter Kontekstual Di Sekolah Dasar: Studi Kasus - A. Renaldi Saputra; Abelia; Endang Khairani; Hairunnisa; Lalu Satriadi; Septiana; Muh. Fahrurrozi; Yul Alfiandi Hadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study analyzes the planning, implementation, assessment, and observed outcomes of the Pancasila Student Profile Strengthening Project (P5) under the Local Wisdom theme through an ecoprint activity among sixth-grade elementary students. A qualitative case-study design was employed at SD Negeri 1 Rumbuk, East Lombok Regency. Informants were selected purposively and included the school principal, the Grade VI-B teacher, and students directly involved in one project cycle. Data were collected through observation, semi-structured interviews, and document analysis, and were analyzed through data condensation, data display, and conclusion drawing and verification. Credibility was strengthened through source triangulation, method triangulation, and the search for disconfirming evidence. The project was planned through contextual theme selection, module development, scheduling, and facilitator-role allocation. Implementation comprised orientation, contextualization–action, and reflection phases. Assessment combined process observation and product evaluation; school documents reported an average ecoprint product score of 3.58 in the good category, although the rubric was not yet fully standardized. Observed outcomes included greater participation, collaboration, creativity, independence, confidence, and appreciation of local culture and the environment. The study contributes a process–product–character model that positions the ecoprint artefact as one source of learning evidence rather than as a single indicator of character change. The findings remain contextual because the study involved a single case and no longitudinal observation.